2019
DOI: 10.11606/s1518-8787.2018052000635
|View full text |Cite
|
Sign up to set email alerts
|

Falls among Brazilian older adults living in urban areas

Abstract: OBJECTIVE To assess the prevalence and factors associated with falls in a nationally representative sample of older Brazilians residing in urban areas.METHODS Data from 4,174 participants (60 years or older) from the baseline of ELSI-Brazil, conducted between 2015 and 2016, were used. The outcome variable was the reporting of one or more falls in the last 12 months. The exploratory variables were sociodemographic characteristics, factors related to the urban environment, and health conditions. Statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
(51 reference statements)
2
18
0
12
Order By: Relevance
“…The prevalence of falls in the past six months was 27.7%, with 19.6% being men and 32.6% being women. These estimations are very close to those reported in a nationwide study by Pimentel et al 2 , who found 18.4% among men and 30.2% among women, although the authors have considered falls in the past 12 months. In addition, an integrative literature review of 35 studies showed that the prevalence of falls among elderly people living in different cities of Brazil ranged from 10.7 to 59.3%, considering the 12-month period before the interview 25. This variation, despite the possible effect of different sampling methods and the operational definition of the variable of interest (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of falls in the past six months was 27.7%, with 19.6% being men and 32.6% being women. These estimations are very close to those reported in a nationwide study by Pimentel et al 2 , who found 18.4% among men and 30.2% among women, although the authors have considered falls in the past 12 months. In addition, an integrative literature review of 35 studies showed that the prevalence of falls among elderly people living in different cities of Brazil ranged from 10.7 to 59.3%, considering the 12-month period before the interview 25. This variation, despite the possible effect of different sampling methods and the operational definition of the variable of interest (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…In Brazil, a study including more than 4,000 elderly individuals (over 60 years old) who lived in urban areas of 70 cities reported that 25.1% had suffered falls in the past 12 months prior to their interviews. Of these, 1.8% had fracture of femur or hip 2 . In addition, the mortality rates increased from 1.25 per 10,000 elderly in 1996 to 3.75 in 2012 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-one studies 12,13,14,15,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60 reported 12-month prevalence of falls, with estimates ranging between 6.5 and 46.9%, and three studies 61,62,63 reported six-month prevalence, of falls, with estimates ranging between 21.5 and 53%. The three remaining studies reported one-month prevalence 64 , three-month prevalence 65 , and lifetime-prevalence 66 of falls (Table 1).…”
Section: Descriptive Analysismentioning
confidence: 99%
“…These events will be monitored closely until a resolution or stabilization is achieved, or until it has been shown that the study intervention is not the cause of the event. According to the recent epidemiologic data of the Brazilian Longitudinal Study of Aging (ELSI-Brazil) [32], if falls incidences during the training session are greater than 25% with 3% resulting in a hip or femur fracture, the study will be interrupted.…”
Section: Adverse Eventsmentioning
confidence: 99%